Taking Interest in Students' Disinterest: Best Practices for Mitigating Amotivation in the Basic Course - Electra Gilchrist-Petty (Central States Communication Association, 2018)
As a general education requirement, basic communication course instructors are afforded the unique opportunity to reach a variety of students. Because many students often are enrolled in the basic communication course out of necessity, student amotivation can transform what should be a dynamic and interactive classroom experience into a daunting challenge that stifles the pedagogical process. To assist in engaging students, 10 best practices for mitigating amotivation in the basic course are presented. By following these best practices, instructors can help cultivate a more engaged and interactive classroom experience for both themselves and their students.